Impact and control of fouling in radioactive environments. (June 2022) - Barton, Franky; Shaw, Samuel; Morris, Katherine; Graham, James; Lloyd, Jonathan R.
Abstract: Fouling and scaling of equipment in the nuclear industry is a significant and challenging problem that effects multiple areas across the entire nuclear fuel cycle. Consequences such as the blockage of fluid flow, accumulation of radionuclides, reduction of heat-transfer energy and enhancement of corrosion, all can have detrimental effects on safety and performance as well as incurring substantial damage and maintenance costs amounting to billions of pounds a year. This review focuses on pipelines and understanding the mechanisms of formation and radionuclide incorporation of inorganic and biological fouling, and microbially influenced corrosion (MIC) mechanisms, as well as exploring prevalent examples in the nuclear industry and parallels in the oil and gas industries. The review will also cover advancements in fouling and scale mitigation and treatment strategies, which are imperative to reduce economic loses and avoid safety hazards in nuclear as well as many other industries. Graphical abstract: Image 1 Highlights: Comprehensive review of fouling of equipment and pipelines across the nuclear fuel cycle. Covers the mechanisms of inorganic and biological scale formation, radionuclide incorporation and MIC. Discusses the impact of fouling on radionuclide accumulation and migration in varied nuclear environments and oil and gas. Evaluates existing and developing scale treatment and mitigation strategies. Continued research is proposed to develop this underrepresented research area to provide safety and economic benefits.